Analisis Penerapan Bea Masuk Anti Dumping oleh Australia terhadap Clear Float Glass Indonesia - Maheralia, Resti (Pusat Pendidikan dan Pelatihan Aparatur Perdagangan, 2024)
Australia has implemented Anti-Dumping Duties (ADD) on import of Clear Float Glass (CFG) from Indonesia since 2011. In the initial imposition, Indonesia was subject to 3.3% - 22.4% ADD, whereas in 2021 Indonesia was subject to 15.3% - 28.3% ADD. Until 2024, it is recorded that Australia has extended the imposition of ADD on CFG originating from Indonesia twice, namely in 2016 and 2021, where the aforesaid imposition will due in 2026. This study intends to elaborate a review of Australia's imposition of CFG ADD in terms of the export performance of Indonesia. This study utilizes a descriptive analysis method based on research sourced from the Australian Anti-Dumping Commission report and related literatures. According to the analysis, it was concluded that Australia's imposition of ADD on CFG products from Indonesia diminishes Indonesia’s CFG export to the Australian market, and on the contrary, there was a raise in Indonesia’s CFG exports to other countries that does not implement ADD. It is expected that the Indonesian government can collaborate optimally with exporters of goods under investigation to defend Indonesia's position during the ongoing anti-dumping investigation.